Efektivitas ekstrak nilam (Pogostemon cablin) dengan tiga metode ekstraksi dan cara aplikasi terhadap hama gudang Tribolium castaneum (Herbst): The effectiveness of patchouli (Pogostemon cablin) extract using three extraction methods and application techniques against the storage pest Tribolium castaneum (Herbst) - Alfina Dellachristi, Veronica; Dadang; Sakti Harahap, Idham (Perhimpunan Entomologi Indonesia, 2025)
The infestation of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) results in the reduction of flour weight, changes in flour color, and a musty odor in stored materials. One alternative control method is using patchouli extract (Pogostemon cablin), which has insecticidal activity. The extraction methods and the application techniques in controlling storage pests influence the effectiveness of the extract as a botanical insecticide. The study aims to examine the differences in yield, composition, content, toxicity, and repellency levels of patchouli extracts obtained using various extraction methods for controlling T. castaneum. The study employs three patchouli extraction methods: maceration, steam-water distillation, and ultrasonic extraction. Three application techniques are used in this study: fumigation, topical and residue. The observed variables include the content and composition of the extraction yield, toxicity levels, and repellency levels. Data analysis is performed using probit analysis to determine LD/LC50 and LD/LC95, and ANOVA at 5% level, followed by Tukey’s test. The research results indicate that the extraction method assisted by ultrasonic waves yields the highest extraction yield. However, patchouli extract obtained through the distillation method exhibits the highest toxicity effects when applied with topical and residue techniques. The LC50 and LC95 values of patchouli extract obtained via distillation are 0.804% and 1.541% while the LD50 and LD95 values are 49.140 μg/imago and 135.729 μg/imago. The main compounds found in patchouli extract obtained through distillation are patchouli alcohol, α-guaiene, δ-guaiene, and seychellene. Patchouli extract obtained through distillation has the potential to act as a contact insecticide and repellent against T. castaneum.